Orientações atuais da Lingüística Histórica brasileira - Silva, Rosa Virgínia Mattos e (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The paper concentrates on the new directions taken by Historical Linguistics in Brazil, which gives special attention to Brazilian Portuguese, studying dialectal and sociolinguistic aspects. A special reference is made to projects that bring together researchers from several universities in the country. (Abstract by Editors (AE)